Regulation of Trophoblast Invasion — A Workshop Report - Knöfler, M.; Simmons, D.G.; Lash, G.E.; Harris, L.K.; Armant, D.R. (Placenta (Eastbourne), 2008)
Trophoblast invasion during placental development helps to establish efficient physiological exchange between maternal and fetal circulatory systems. Trophoblast stem cells differentiate into multiple subtypes, including some that are highly invasive. Signalling to the trophoblast from decidua, uterine natural killer cells and vascular smooth muscle can regulate extravillous trophoblast differentiation. Important questions remain about how these cellular interactions promote trophoblast invasion and the signalling pathways that are involved. New and established biological models are being used to experimentally examine these interactions and the underlying molecular mechanisms.